Pengembangan Desa Surau Sebagai Desa Wisata Berkelanjutan - Sri Handayani Hanum; Nurhayati Darubekti; Hajar G. Pramudyasmono; Panji Suminar; Sumarto Widiono (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Indonesia has 74,093 villages and as many as 1,073 villages have the potential to be developed into tourist villages. Surau Village, Bengkulu Province, is one of the villages that has the potential to be developed into a tourist village. The results of mapping the natural potential that can be developed into leading tourist destinations have been carried out and it is agreed that there are six locations that can be developed into tourist destinations, namely Blue Lake, Silver Bridge, White Napal Hill, Geothermal Springs, Waterfalls, Lubuk Vi. Pioneering efforts towards a tourist village have been carried out by the local village government since 2020, but its development has encountered various challenges. Results of PKM activities: implementation of social preparations and agreements on the development of Surau Village as a tourist village, the implementation of grants for physical facilities/facilities that support the attraction of tourism objects, the implementation of mutual cooperation in the construction of physical facilities/facilities in the Rindu Hati River border area and Lubuk Vi, and an increase in the performance and capability of the management and organization of Pokdarwis Widesu. Further assistance is needed from academics as one of the tourisms pentahelix, the media that play a role in forming positive public opinion and information dissemination, and the community that plays a role in realizing Sapta Pesona.